Reading Lies Nonverbal Communication and Deception. [article]. - Vrij, Aldert
The relationship between nonverbal communication and deception continues to attract much interest, but there are many misconceptions about it. In this review, we present a scientific view on this relationship. We describe theories explaining why liars would behave differently from truth tellers, followed by research on how liars actually behave and individuals? ability to detect lies. We show that the nonverbal cues to deceit discovered to date are faint and unreliable and that people are mediocre lie catchers when they pay attention to behavior. We also discuss why individuals hold misbeliefs about the relationship between nonverbal behavior and deception?beliefs that appear very hard to debunk. We further discuss the ways in which researchers could improve the state of affairs by examining nonverbal behaviors in different ways and in different settings than they currently do. -- (from the author)